1986
DOI: 10.1002/bjs.1800730509
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric bile acids and histological changes in gastric mucosa

Abstract: Multiple gastric biopsies and gastric juice aspirates were taken in 108 patients undergoing routine or review gastroscopy for a variety of upper gastrointestinal disorders. The gastric juice was measured for free and total bile acids and the biopsies examined for premalignant mucosal changes. Total bile acid levels were significantly higher in patients with atrophic gastritis, intestinal metaplasia and dysplasia but not chronic gastritis. There was no correlation between the severity of the dysplasia and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Houghton et al [29] found a good correlation between TBA concentration and atrophic gastritis, intestinal metaplasia and dysplasia but the majority of their patients were postoperative. In our series of intact stomachs, there were no significant correla tions between bile reflux and the presence of atrophic gastritis or intestinal metaplasia in H. pylori -ve elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Houghton et al [29] found a good correlation between TBA concentration and atrophic gastritis, intestinal metaplasia and dysplasia but the majority of their patients were postoperative. In our series of intact stomachs, there were no significant correla tions between bile reflux and the presence of atrophic gastritis or intestinal metaplasia in H. pylori -ve elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intragastric mutagens also may be synthetized in the non-atrophic, acidic stomach from primary amines, phenolic or other aromatic compounds. [67][68][69] Reflux of bile into the stomach is another potential inducer of intestinal metaplasia 70 but, for this action, the synergistic influence of the underlying gastritis may also be necessary. In subjects not carrying H. pylori, intragastric bile is not capable of inducing intestinal metaplasia 71,72 even though there is evidence that bile can induce cancers in animals without other contributing factors.…”
mentioning
confidence: 99%
“…Mosimann et al 11 found a significant association between a gastric pH greater than 4, positive duodenagastric reflux as ascertained by the scintigraphic technique, and the presence of gastric dysplasia in 36 asymptomatic patients who had undergone duodenal ulcer surgery 7 or more years earlier. Finally, Houghton et al 3 conducted an endoscopic biopsy and gastric aspirate study in 108 patients and found that the total bile acid concentration was significantly higher in the 70 patients with gastric dysplasia than in the other 38 patients (P=O.OI, Mann-Whitney U test).…”
Section: Discussionmentioning
confidence: 99%